Series of Nusantara Folklore Storybooks as the Media for Extensive Reading for Indonesia Elementary Students - Rochmatika Nur Anisa (ELT in Focus, 2019)
Reading the series of storybooks for Young Learners (YLs) promotes the vocabulary development. Incidental learning and direct teaching the words can develop them. Therefore, the reading materials become essential to be provided. As the English becomes extracurricular   at elementary schools in Indonesia, the opportunity to use the English language by activating all four skills is necessary. As for reading, the YLs can get the experience by reading different reading texts ranging from simple signage to long stories. In addition, the Series of Nusantara Folklore storybooks is recommended to choose by teachers because it assists YLs learning principles that are interesting and authentic. In a nutshell, the series of storybook is a special package of narrow reading to support the extensive reading in English for Young Learners (EYL).